Афілофороїдні гриби Регіонального ландшафтного парку «Ізюмська лука» та прилеглих територій (Харківська область, Україна) - Ординець, Олександр Володимирович; Акулов, Олександр Юрійович; Усіченко, Андрій Сергійович (Чорноморський ботанічний журнал, 2012)
Two hundred and eight species of aphyllophoroid fungi (Basidiomycota) were revealed by us in “Iziumska luka” Regional Landscape Park and vicinities (Ukraine, Kharkiv region, Steppe natural zone) during 2007-2010. Of them, 202 species are firstly reported for the research area. Fourteen species are revealed for the first time in Ukraine. They are Athelia bombacina (Link) Pers., A. salicum Pers., Boidinia furfuracea (Bres.) Stalpers et Hjortstam in Hjortstam et Stalpers, Ceraceomyces tessulatus (Cooke) Jülich, Hypochnicium geogenium (Bres.) J. Erikss., Loweomyces fractipes (Berk. et M.A. Curtis) Jülich, Phellinus rhamni (Bondartseva) H. Jahn, Piloderma lapillicola Jülich, Sistotrema resinicystidium Hallenb., S. sernanderi (Litsch.) Donk, Trechispora praefocata (Bourdot et Galzin) Liberta, Tulasnella pinicola Bres., T. pruinosa Bourdot et Galzin and Vuilleminia cystidiata Parmasto. In the case of 4 species, i.e. Fibriciellum silvae-ryae J. Erikss. et Ryvarden, Hyphodontia tuberculata Kotir. et Saaren., Sistotremella hauerslevii Hjortstam and Trechinothus smardae (Pilát) E.C. Martini et Trichies, “Iziumska luka” is the first and still single area of occurrence reported from the Eastern Europe. Together with 1 species known from the research territory before our study, the total list of aphyllophoroid fungi of this forest massif now comprises 209 species and is presented in the paper with information on their substrata. Remarks are provided both for taxonomically and mycofloristically important records.
Aphyllophoroid fungi of “Iziumska luka” Regional Landscape Park and adjacent areas (Kharkiv region, Ukraine)
Афиллофороидные грибы Регионального ландшафтного парка «Изюмская лука» и сопредельных территорий (Харьковская область, Украина)
Keywords: Basidiomycota; aphyllophoroid fungi; biodiversity; Ukraine